Protecting our coast for everyone's future: Indigenous and scientific knowledge support marine spatial protections proposed by Central Coast First Nations in Pacific Canada. Issue 5 (20th July 2022) - Reid, Mike; Collins, Muxvpenstista Lena; Hall, Smawn Richard J.; Mason, Ernest; McGee, Gord; Frid, Alejandro
Abstract: We, the Haíłzaqv, Kitasoo Xai'xais, Nuxalk and Wuikinuxv First Nations, are the traditional stewards of our territories in the Central Coast of British Columbia, Canada. Our traditional laws obligate us to manage and protect our territories for current and future generations. Spatial management is inherent to our cultures through the Hereditary Chief governance system, in which specific people within a lineage inherit the rights and responsibilities for stewarding specific areas. Since the 19th century, we have been experiencing cultural disruptions caused by settler colonialism, which are now worsened by the declines of marine species vital to our cultures. These declines reflect fishery impacts exacerbated by climate change. Western fisheries management focuses on maximum sustained yields (MSY), ignoring body size declines that disrupt food webs and diminish population productivity for vertebrate and invertebrate taxa, thereby eroding resilience to climate change. The worldview encompassed by the MSY framework— take the most that you can without compromising future exploitation while assuming no environmental change —is the antithesis of ours— take only what you need and leave lots for the ecosystem . Furthermore, standard stock assessments do not account for uncertainties inherent to climate change effects on distributions and productivity, and many by‐catch species are unassessed. Consistent with our traditional knowledge, scientific evidence indicates that marine protected areas (MPAs), coupled with other measures to reduce fishing mortality, can restore exploited species, safeguard biodiversity and contribute to fisheries sustainability. In the 2000s, we paired Indigenous knowledge and Western science to develop marine spatial plans. These plans are foundational in our contribution to the ongoing development of the Marine Protected Area Network for Canada's Northern Shelf Bioregion (MPAN‐NSB), for which we are co‐governance partners with 14 other First Nations and the governments of Canada and British Columbia. Our proposed spatial protections for the MPAN‐NSB encompass areas important to many exploited taxa and to corals, sponges, eelgrass beds and other carbon stores. Their implementation would fill conservation gaps which have persisted under current fishery management. Given our history of spatial management through the Hereditary Chief governance system, the MPAN‐NSB is a culturally appropriate way forward for marine conservation in our territories. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.